PZT-like structural phase transitions in the BiFeO3–KNbO3 solid solution1. Issue 23 (21st June 2015) - Lennox, Robert C.; Taylor, Daniel D.; Vera Stimpson, Laura J.; Stenning, Gavin B. G.; Jura, Marek; Price, Mark C.; Rodriguez, Efrain E.; Arnold, Donna C.
<x xml:space="preserve">Abstract</x> The solid solution between bismuth ferrite and potassium niobate indicates a similar series of phase transitions to PZT.